Assessment of knowledge, attitude, and practices of Indian medical and engineering students on COVID-19: A nation-wide online survey - Bhagyajyoti Priyadarshini; Himel Mondal; Shiba Sai Swarup; Joshil Kumar Behera; Akankhya Panigrahi; Ankan Basu (Journal of Applied Sciences and Clinical Practice, 2023)
Background: Coronavirus disease (COVID-19) has created fear, misconceptions, and apprehensions among the public including the youth of the society. We evaluated and compared the knowledge, attitudes, and practices toward COVID-19 among undergraduate medical and engineering students of India. Methods: An online cross-sectional survey was carried out on Indian undergraduate medical and engineering students in September 2020. A prevalidated and pretested questionnaire was used in this study. The questionnaire had eight items for knowledge, six items for attitudes, and four for practices. A snowball sampling method was used to collect data. Results: A total of 1757 (1137 [64.71%] medical, 620 [35.29%] engineering) Indian students participated in the study. The overall scores of knowledge were 5.77 ± 1.2, the attitude was 5.06 ± 0.83, and practices were 2.32 ± 0.93 (analysis of variance P < 0.0001). There was no gender difference in knowledge, attitude, or practice. The medical student scored higher in knowledge (P < 0.0001) and attitude (P < 0.0001) compared to engineering students. Medical students showed a significant positive correlation (r = 0.13, P < 0.001) of attitude with semester of study. Engineering students showed significant positive correlation of knowledge (r = 0.12, P = 0.002) and practice (r = 0.11, P = 0.008) with semester of study. Conclusion: Indian medical and engineering students had a good level of knowledge and positive attitudes towards COVID-19. Although medical students scored higher in knowledge and attitude, the practice showed no difference. The practice scores were the lowest among the three parameters. This reaffirms the need for more strategic planning to ensure good practices among students of both the major sectors of science.